Surface Study of Cu2SnS3 Using First‐Principles Density Functional Theory. Issue 6 (21st April 2021) - Dahule, Rohit; Raghav, Abhishek; Hanindriyo, Adie Tri; Hongo, Kenta; Maezono, Ryo; Panda, Emila
Abstract: Here, the electronic structure of monoclinic Cu2 SnS3 (CTS) along with the surface energy and surface electronic structure of (200) and ( 1 ¯ 31) terminated surfaces are computed using density functional theory (DFT). Moreover, this computation is carried out using the Heyd–Scuseria–Ernzerhof (HSE) hybrid functional after geometry optimization of ions performed using local density approximation (LDA). Surface distortion is seen for both these considered CTS surfaces after geometrical optimization of these surface supercells. In (200) surface supercell, Cu and Sn atoms are seen to move inwards, and outwards respectively, whereas, for ( 1 ¯ 31) surface supercell, S atoms show high lateral displacement. Moreover, the relaxation effect of subsurface ions results in the displacement of 0.1 Å, which further reduced beyond the second layer for (200) surface supercell, whereas, ( 1 ¯ 31) surface shows the random displacement of the subsurface ions. Moreover, the surface energy of (200) and ( 1 ¯ 31) surfaces are calculated to be 0.0292 and 0.3106 eV Å −2, respectively, indicating (200) being the more stable CTS surface. Furthermore, the valence and conduction band edges of these surfaces are found to overlap, suggesting metallic characteristics for these surfaces contrary to the semiconducting behavior found for the bulk CTS (with the calculated band gap of 0.78 eV). Abstract : First‐principles calculations are implemented to analyze the effect of surface relaxation, surface energy, and the electronic structure of (200) and ( 1 ¯ 31) Cu2 SnS3 surfaces.